Community Empowerment to Reduce Blood Glucose Levels of Diabetes Mellitus Clients Through The Provision of Guava Leaves (Psidium Guajava) Decoction in Tuladenggi Sub-District, Dungingi District - Lisdiyanti Usman; Mansyur Tomayahu; Suwarly Mobiliu; Kartin L. Buheli (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Diabetes Mellitus is a chronic metabolic condition caused by insufficient insulin produced by the pancreas or the body's inability to effectively utilize insulin. Diabetes has become more common in low- and middle-income countries during the previous decade. In 2018, Gorontalo Province ranked eighth in Indonesia for the highest prevalence of Diabetes Mellitus. According to the findings of the 2018 Basic Health Research (Riskesdas), the prevalence of non-communicable diseases (NCDs) in Gorontalo Province has increased compared to Riskesdas 2013. Based on data from Gorontalo Province Department of Health, cancer prevalence increased from 1.4 percent in 2013 to 1.8 percent in 2018. The prevalence of stroke increased from 7 percent to 10.9 percent, and the prevalence of chronic kidney disease increased from 2 percent to 3.8 percent. Next, diabetes mellitus increased from 6.9% to 8.5 percent, whereas hypertension increased from 31% to 34.1 percent. Gorontalo are placed in the top 10 nationally in Indonesia due to of the increasing frequency of non-communicable diseases. Hence, the Government established an Integrated Development Post (Posbindu) for non-communicable diseases. The purpose of community service is to determine the effect of giving decoction from guava leaves (psidium guajava) on blood glucose levels in diabetes mellitus clients in Dungingi sub-district, Gorontalo City. The results of a community service project carried out from August 10 to September 1, 2021, with 100 participants, revealed that 62 people saw a significant decline after a one-week intervention. On the other hand, for those who do not experience any effect, may be due to irregular and non-routine consumption of guava leaves decoction.